Measurement of Background Ionizing Radiation Level and Dose Risk Around Nigeria’s First Oil Well, Otuabagi, Oloibiri Clan, Bayelsa State, South-South, Nigeria - Biere, P. E.; Ogobiri, G. E.; Meindinyo, R. O. K.; James, J.; Abule, E.; Emumejaye, K. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2024)
Individuals who get exposed to radiation stand the danger of experiencing health problems such as skin burn, acute radiation syndrome, cardiac condition. Natural radiation chains exist in nature including oil and gas fields in the ground. Therefore, crude may contain natural radioactivity. In this study, the background ionizing radiation level around the immediate vicinity of Nigeria’s first oil well has been measured using the Radalert-100X, a potable radiation detector. The background exposure rate ranges from 0.0095 to 0.0155 mRh-1 with a mean of 0.0128 mRh-1. The absorbed dose rate calculated ranges from 82.65 to 156.6 nGyh-1 with a mean of 109.56 nGyh-1. The averages of the annual effective dose equivalent ranges from 0.101 to 0.192 mSvy-1 with a mean of 0.136 mSvy-1. The calculated averages of ELCR from the study area ranges from 0.359 x 10-3 to 0.670 x 10-3 with a mean of 0.476 x 10-3. From the evaluation made, the granite area around the well head, has the highest background ionizing radiation value and other parameters compared to results from the well head and the muddy area. Given the values recorded in the study, it is imperative to advise that appropriate precautions be taken, such as adhering to the ALARA principle, to shield the public from radiation related risks.